2016
DOI: 10.1002/chem.201504435
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Generation of ArCu from CuF2 Makes Coupling of Bulky Aryl Silanes Feasible and Highly Efficient

Abstract: A bimetallic system Pd/CuF2, catalytic in Pd and stoichiometric in Cu, is very efficient and selective for the coupling of fairly hindered aryl silanes with aryl, anisyl, phenylaldehide, or pyridyl iodides of conventional size. The reaction involves the activation of the silane by Cu II followed by disproportionation and transmetalation from the Cu I (aryl) to Pd II , on which coupling takes place. The Cu III formed in the disproportionation is reduced to Cu I (aryl) by the aryl silane in excess, so that the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 90 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, addition of CuF 2 or CuF 2 /TTMPP to a mixture of 11 and CsF did not affect the yields of 4 a and 12 . Of note, with CuF 2 , the homo‐coupled products, namely bis(thiophene)s, were not observed at all, suggesting that the formation of Ar−Cu I complexes may be excluded . Although the exact behavior of CuF 2 is unclear yet, it may be assumed to assist transmetalation between the silicate and a palladium complex by reversible formation of Ar−CuX 2 or Ar−CuX species …”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, addition of CuF 2 or CuF 2 /TTMPP to a mixture of 11 and CsF did not affect the yields of 4 a and 12 . Of note, with CuF 2 , the homo‐coupled products, namely bis(thiophene)s, were not observed at all, suggesting that the formation of Ar−Cu I complexes may be excluded . Although the exact behavior of CuF 2 is unclear yet, it may be assumed to assist transmetalation between the silicate and a palladium complex by reversible formation of Ar−CuX 2 or Ar−CuX species …”
Section: Figurementioning
confidence: 98%
“…[21] Of note,with CuF 2 ,the homo-coupled products,namely bis(thiophene)s,were not observed at all, suggesting that the formation of ArÀCu I complexes may be excluded. [22] Although the exact behavior of CuF 2 is unclear yet, [23] it may be assumed to assist transmetalation between the silicate and apalladium complex by reversible formation of Ar À CuX 2 or Ar À CuX species. [24] In conclusion, we have developed aP d/Cu dual catalyst system for the cross-coupling of aryl(trialkyl)silanes with bromoarenes under mild conditions.Awide variety of silyl groups,s uch as SiMe 3 ,S iEt 3 ,S iMe 2 (t-Bu), and Si(i-Pr) 3 ,a s well as various aryl groups are compatible with these reaction conditions.T he stability of the trialkylsilyl groups allows for as equential C À Ha rylation/cross-coupling process using am onosilylthiophene to generate an unsymmetric diarylthiophene.Moreover,the present cross-coupling is applicable to polyarylene synthesis.W ea re now focusing on extending this concept to aryl silanes,e specially those containing electron-rich and -neutral aryl groups,a nd elucidating the reaction mechanism.…”
mentioning
confidence: 99%
“…The spectroscopic data are in accordance with those reported. 21 Colorless oil; yield: 84 mg (40%); R f = 0.45 (hexane).…”
Section: 44′6-tetramethylbiphenyl (22)mentioning
confidence: 99%
“…10 Casares et al found that, in the coupling of arylalkoxysilanes, CuF 2 greatly accelerated the reaction process so that the catalytic activity was enhanced. 11 It is known that, by controlling the size and dispersion of the cocatalyst, and establishing the appropriate connection between the cocatalyst and the photocatalyst, the photocatalytic activity can be expected to significantly improve due to the low energy barrier and high charge transfer in the interface. 12 The simple fabrication of effective-contacted heterojunctional photocatalysts is an effective way to solve the problem.…”
Section: Introductionmentioning
confidence: 99%